A tumor-restricted glycoform of podocalyxin is a highly selective marker of immunologically cold high-grade serous ovarian carcinoma - Brassard, Julyanne; Hughes, Michael R.; Dean, Pamela; Hernaez, Diana Canals; Thornton, Shelby; Banville, Allyson C.; Smazynski, Julian; Warren, Mary; Zhang, Kevin; Milne, Katy; Gilks, C. Blake; Mes-Masson, Anne-Marie; et al. (Frontiers in Oncology, 2023)
Introduction Targeted-immunotherapies such as antibody-drug conjugates (ADC), chimeric antigen receptor (CAR) T cells or bispecific T-cell engagers (eg, BiTE®) all aim to improve cancer treatment by directly targeting cancer cells while sparing healthy tissues. Success of these therapies requires tumor antigens that are abundantly expressed and, ideally, tumor specific. The CD34-related stem cell sialomucin, podocalyxin (PODXL), is a promising target as it is overexpressed on a variety of tumor types and its expression is consistently linked to poor prognosis. However, PODXL is also expressed in healthy tissues including kidney podocytes and endothelia. To circumvent this potential pitfall, we developed an antibody, named PODO447, that selectively targets a tumor-associated glycoform of PODXL. This tumor glycoepitope is expressed by 65% of high-grade serous ovarian carcinoma (HGSOC) tumors. Methods In this study we characterize these PODO447-expressing tumors as a distinct subset of HGSOC using four different patient cohorts that include pre-chemotherapy, post-neoadjuvant chemotherapy (NACT) and relapsing tumors as well as tumors from various peritoneal locations. Results We find that the PODO447 epitope expression is similar across tumor locations and negligibly impacted by chemotherapy. Invariably, tumors with high levels of the PODO447 epitope lack infiltrating CD8+ T cells and CD20+ B cells/plasma cells, an immune phenotype consistently associated with poor outcome. Discussion We conclude that the PODO447 glycoepitope is an excellent biomarker of immune “cold” tumors and a candidate for the development of targeted-therapies for these hard-to-treat cancers.